Peningkatan Kompetensi Profesional Guru Melalui Digitalisasi Pembelajaran di Pendidikan Menengah Kejuruan - Ahmad Ridoh; Fattachul Huda Aminuddin; Tri Wiyoko; Yogi Irdes Putra; Thomas Adrino Putra; M. Azwan (I-Com: Indonesian Community Journal, 2024)
Innovation in the use of technology media by MGMP teachers of vocational subjects in learning is still relatively low due to teachers' lack of training and experience to innovate in teaching. So, there needs to be a community service activity that aims to improve teacher competence through digitalization of learning by emphasizing the use of technology and digital learning platforms. In August, this activity was carried out at campus II of the Muhammadiyah University of Muara Bungo. The implementation of this community service activity uses the service learning method, which is divided into three stages, namely planning, implementation, and evaluation. The results of the community service to improve teacher professional competence through the digitalization of learning have been carried out by providing training in Canva media and e-learning media using Moodle. The training provided can improve teachers' understanding and skills in operating Canva and Moodle. Evaluation of the training shows that there are benefits obtained by teachers that can be applied in schools and can improve teacher professionalism in terms of mastery of technology and information.